Assessing the Consequences of Ethno-Religious Violence on Farming Activities in Jos Plateau State, Nigeria - Shipurut, Geoffrey Nanbal; Danasabe, Dankano Chonwa; Damian, Gana Chuseh (Darul Yasin Al Sys, 2025)
Ethno-religious violence in Jos, Plateau State severely hampers farming activities, causing reduced production, farmer displacement, and destruction of infrastructure. These challenges deepen poverty and food scarcity, necessitating urgent remedial actions. The study used a descriptive, cross-sectional survey research design. A sample size of 400 respondents was selected from the total population of 1,260,200 using the Tare Yamane formula. Questionnaires were distributed to 400 randomly selected respondents across Jos North, Jos South, and Jos East LGA. Interviews were also conducted with six key informants to complement the data gathered from the questionnaires. Responses from the questionnaires were analysed using descriptive statistics of frequency counts and percentages. Quantitative data were analysed while outlining the key point presented by the key informant. The study revealed that ethno-religious violence in Jos Plateau State disrupts farming through reduced production, displacement of farmers, and destruction of infrastructure. Trauma leads to poverty, hunger, and impaired farm management. The study recommended that addressing ethno-religious conflict in Jos Plateau requires improved security, conflict resolution, and emergency aid for displaced farmers. Rehabilitation efforts should prioritise rebuilding infrastructure, financial support, resettlement, and mental health services for affected farmers.